Markers of Malnutrition among Dialysis Naïve CKD Patients in North Central Nigeria - Sulaiman, Yarima Y; Dunga, Jacob A; Musa, Jafiada J; Yakubu M Adamu; Abubakar, Auwal M; Liman, Haruna Usman; Vakkai, Innocent; Sahabi, Muhammad A; Zawaya, Kefas P; Vandi, Zira G; et al. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Chronic kidney disease (CKD) has a major effect on global health, it is responsible for both direct cause of global morbidity and mortality and as an important risk factor for Malnutrition and cardiovascular disease. In Nigeria, CKD accounts for 2-8% of total admissions into tertiary Hospital. Methods: This is a cross-sectional study aimed at determining markers of malnutrition such Subjective global assessment (SGA), Body mass index (BMI), waist circumference (WC), Hip circumference (HC), Mid-Arm Muscle Circumference (MAMC), Triceps Skin Fold Thickness (TSFT) serum albumin, serum creatinine, total protein, serum cholesterol C-reactive protein (CRP) and correlating them among CKD patients as a determinant of malnutrition among these group of patients. Individuals between the ages of 16 – 60 years, Patients with confirmed CKD were recruited for this research. Blood samples were drawn from a forearm vein where the plasma was separated from the cells by centrifugation and the plasma was analyzed for all the variables indicated. Results: There were more cases of patient with low BMI among CKD patients and this was also observed more among Diabetes mellitus (DM) patient with CKD and the non-DM patient. There were 9 (31%) of diabetics versus 5 (6.3%) of non-diabetics had low BMI. OR = 6.6, 95% CI = 2.00 – 22.10; P = 0.0001. There exists no liner relationship between serum albumin to SGA. The r2 = 0.11. There were 4 (80%) of patients with CRP >7.5mg/l and serum albumin level of <28g/l. This study also showed that 19 (18.4%) had CRP < 7.5mg/l and serum albumin < 28g/l suggesting evidence of malnutrition despite low CRP level, while 84 (81.6%) had CRP < 7.5mg/l and serum albumin >28g/l. This shows that there is a negative correlation between CRP and serum albumin levels. OR = 17.68, 95% CI = 1.87 – 16>, P= 0.03. Conclusion: Kidney disease is a major risk for malnutrition among patients and correlation between anthropometric indices, serum albumin and CRP will help determine the risk of CKD among patients.